2019
DOI: 10.1142/s021820251950057x
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Sobolev regularity and rate of approximation of the obstacle problem for the integral fractional Laplacian

Abstract: We obtain regularity results in weighted Sobolev spaces for the solution of the obstacle problem for the integral fractional Laplacian (−∆) s . The weight is a power of the distance to the boundary that accounts for the singular boundary behavior of the solution for any 0 < s < 1. These bounds then serve us as a guide in the design and analysis of an optimal finite element scheme over graded meshes.definitions of the operator (−∆) s , motivated by applications, here we choose the so-called integral one; that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 46 publications
(68 reference statements)
3
20
0
Order By: Relevance
“…Note that due to the strong boundary singularity of the solution the adaptive refinement is particularly strong near the boundary, as well as near the free boundary. This observation underlines the recent analysis of the obstacle problem in [12]. Figure 7 shows the error in the H s (Ω) norm for the different meshes in terms of the degrees of freedom.…”
Section: Time-independent Problemssupporting
confidence: 78%
See 3 more Smart Citations
“…Note that due to the strong boundary singularity of the solution the adaptive refinement is particularly strong near the boundary, as well as near the free boundary. This observation underlines the recent analysis of the obstacle problem in [12]. Figure 7 shows the error in the H s (Ω) norm for the different meshes in terms of the degrees of freedom.…”
Section: Time-independent Problemssupporting
confidence: 78%
“…This behaviour has been exploited in [2] who showed that the solution admits 1+s−ε derivatives in an appropriate weighted Sobolev space. For further discussion of the expected regularity of solutions of variational inequalities, see [13], as well as [11,12] for refined estimates in the case of the nonlocal obstacle problem.…”
Section: A Priori Error Estimates For Variational Inequalitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…We refer to the survey [9] for additional discussion, comparison of methods, and references. Moreover, the fractional obstacle problem for (−∆) s has been studied in [11,13,17], where regularity estimates and convergence rates are derived.…”
Section: Introductionmentioning
confidence: 99%